The effects of cave exploration activity towards Kilim Geoforest Park, Langkawi, Malaysia - Mohd Ismail, Widad; Ibrahim, Putri Haryati; Mansor, Mazlina (Penerbit UTM Press, 2021)
There are many natural geological heritage sites located in Kilim, as the total area of the geoforest consists of karst rock that was formed 500 million years ago. Bat Cave is among the favourite spot for tourists to appreciate and explore geological heritage sites. The Bat Cave is a-200 million years’ minerals formation site and a habitat for thousands of bats in the geoforest area. However, excessive tourism activities have affected various natural resources and wildlife habitats of Kilim Karst Geoforest Park, Langkawi. The Bat Cave is one of the geological sites that are most probably affected by tourism activities. The aim of this paper is to identify local residents' and tourists’ opinions on the effects of cave exploration and tourism activities on the habitat of bats and geo-physical characters of the Bat Cave, Kilim Karst Geoforest Park, Langkawi. The methodology employed in this study is based on questionnaire survey with a 93% response rate (n=299). Questionnaires were distributed to tourists (65), local residents in Kilim (145), and staff (89) who are in charged in the tourism operation of Kilim Karst Geoforest Park. Findings of this study suggest that tourism activities such as cave exploration and sight-seeing activities caused deterioration towards the physical characteristics of natural resources and habitat of bats in the Bat Cave, Kilim Karst Geoforest Park, Langkawi. This is due to tourists not adhering to a proper procedure (e.g. frequent use of torchlight) while exploring the cave. Respondents agree that there is a decline in the numbers of the bat population in the cave. The management agency of Kilim Karst Geoforest Park needs to take steps in controlling or reducing the number of tourist arrivals by using the tourism carrying capacity approach in order to promote stability. The exceeded population could cause destructions towards the resources. Degradation of natural resources indirectly would distract the natural symbiosis of the ecosystem.